1984
DOI: 10.1002/path.1711440410
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface characterization of the human osteoclast: Phenotypic relationship to other bone marrow‐derived cell types

Abstract: Among the differentiated progeny of stem cells transplantable by bone marrow are osteoclasts, the multinucleate cells which are the major agents of bone resorption. Although the osteoclast is well characterized from a structural and functional standpoint, its development and origin are still far from clear. We have used monoclonal antibodies to investigate the interrelationship between osteoclasts and other haemopoietic cells in man. We have analysed the distribution of 19 granulocyte-monocyte antigens in eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

1985
1985
1996
1996

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 22 publications
2
32
0
1
Order By: Relevance
“…After a limited number of mouse alveolar macrophages (8- (15,16), the absence of calcitonin receptors and responsiveness in macrophages (17,18), and differences in membrane phenotypic expression between macrophages and osteoclasts (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…After a limited number of mouse alveolar macrophages (8- (15,16), the absence of calcitonin receptors and responsiveness in macrophages (17,18), and differences in membrane phenotypic expression between macrophages and osteoclasts (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these cells had a fibroblastic morphology; rounded mononuclear cells and some multinucleated giant cells were also present. However, many of these multinucleated cells were macrophage polykaryons judged by their strong expression of HLA-DR and CDllc (Horton et al, 1984;Athanasou et al, 1992) as well as their low or undetectable levels of VNR and TRAP; such cells were not observed in the original tissue. After 15 days of culture, large numbers of these outgrown cells were present, and were confluent on the surface of the plastic within 21 days of culture.…”
Section: Effects Of Gctb-conditioned Medium On Cbmmentioning
confidence: 93%
“…Not only have they been found to have a protective action on the mineral component of bone, but have also been seen to inhibit osteoclast function [2,3]. The origin of osteoclasts from hematopoietic precursors is still controversial, yet it has been reported that they belong to the mononuclear phagocytic cell line [4,5], These compounds have been described as inhibitors of multinucleated cell precursors in the bone marrow culture system [6] [14], these biological parameters were considered in the evaluation of the effects of BPs on the MO. The effects of these drugs on phagocytosis was studied in two in vitro mod els which differed in their mechanism of in gestion.…”
Section: Introductionmentioning
confidence: 99%